Cilostazol Upregulates Autophagy via SIRT1 Activation: Reducing Amyloid-β Peptide and APP-CTFβ Levels in Neuronal Cells - Lee, Hye Rin (PLoS One, 2015)
Autophagy is a vital pathway for the removal of β-amyloid peptide (Aβ) and the aggregated proteins that cause Alzheimer’s disease (AD). We previously found that cilostazol induced SIRT1 expression and its activity in neuronal cells, and thus, we hypothesized that cilostazol might stimulate clearances of Aβ and C-terminal APP fragment β subunit (APP-CTFβ) by up-regulating autophagy.When N2a cells were exposed to soluble Aβ1–42, protein levels of beclin-1, autophagy-related protein5 (Atg5), and SIRT1 decreased significantly. Pretreatment with cilostazol (10–30 μM) or resveratrol (20 μM) prevented these Aβ1–42 evoked suppressions. LC3-II (a marker of mammalian autophagy) levels were significantly increased by cilostazol, and this increase was reduced by 3-methyladenine. To evoke endogenous Aβ overproduction, N2aSwe cells (N2a cells stably expressing human APP containing the Swedish mutation) were cultured in medium with or without tetracycline (Tet(+) for 48 h and then placed in Tet(-) condition). Aβ and APP-CTFβ expressions were increased after 12~24 h in Tet(-) condition, and these increased expressions were significantly reduced by pretreating cilostazol. Cilostazol-induced reductions in the expressions of Aβ and APP-CTFβ were blocked by bafilomycin A1 (a blocker of autophagosome to lysosome fusion). After knockdown of the SIRT1 gene (to ~40% in SIRT1 protein), cilostazol failed to elevate the expressions of beclin-1, Atg5, and LC3-II, indicating that cilostazol increases these expressions by up-regulating SIRT1. Further, decreased cell viability induced by Aβ was prevented by cilostazol, and this inhibition was reversed by 3-methyladenine, indicating that the protective effect of cilostazol against Aβ induced neurotoxicity is, in part, ascribable to the induction of autophagy. In conclusion, cilostazol modulates autophagy by increasing the activation of SIRT1, and thereby enhances Aβ clearance and increases cell viability.